Lifelong Learning on the Go: English Language Mobile Learning in China. Issue 162 (18th June 2019) - Kang, Haijun; Lin, Xi
Abstract: As China is playing an active role in the World's politics, economy, and cultural circles, being able to communicate in English has become one of the basic life and work skills and a key for global access and integration. High mobile technology penetration, together with the proliferation of mobile learning applications, have made it possible for Chinese adult learners to learn English on the go. Mobile technology's core features including portability, instant power‐on, on‐demand, and the ability to accommodate multimodal learning styles and preferences are accounted for to describe mobile learning apps' affordances for lifelong adult learners' English learning. Four popular English language learning apps, are compared to illustrate how Chinese lifelong adult learners are learning English on the go.